2004
DOI: 10.1890/02-0752
|View full text |Cite
|
Sign up to set email alerts
|

Disturbances as a Structuring Factor of Plant Palatability in Aquatic Communities

Abstract: Abstract. Plant palatability plays an important part in the fitness of species and is therefore regarded as a key functional trait. The aim of this study was to relate the palatability of aquatic macrophytes to their distribution in riverine wetlands differing in their exposure to spate flood disturbances. Thirty-three former channels of the Rhô ne River Basin (eastern France) were characterized in terms of flood-disturbance level. Nutrient richness was also measured to eliminate its potential confounding effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 50 publications
0
43
0
Order By: Relevance
“…, 2001). We have also observed that the most palatable macrophyte species are frequent in disturbed environments (Elger, Barrat‐Segretain & Amoros, 2002; Elger et al. , 2004; Elger & Lemoine, 2005).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…, 2001). We have also observed that the most palatable macrophyte species are frequent in disturbed environments (Elger, Barrat‐Segretain & Amoros, 2002; Elger et al. , 2004; Elger & Lemoine, 2005).…”
Section: Discussionmentioning
confidence: 56%
“…This was particularly obvious for Sagittaria sagittifolia , which occurred in all the control mesocosms, but failed to establish in any of the grazer‐stocked mesocosms. In a previous palatability trial, this species was the most consumed among 40 macrophyte species tested (Elger et al. , 2004).…”
Section: Discussionmentioning
confidence: 88%
“…In calcareous groundwater-supplied ecosystems, the composition of plant communities has been shown to depend mainly on the phosphate and ammonium concentrations in the water (Carbiener et al 1990;Elger et al 2004). The selection of the 4 streams was consequently based on both (1) the occurrence of vegetation groups considered as representative of increasing nutrient levels, and (2) the phosphate and ammonium concentrations in the water.…”
Section: Nutrient Stressmentioning
confidence: 99%
“…drought or waterlogging; Ernst, 1990;Capon, 2003) and biotic interactions (i.e. interspecific competition for light or nutrients; Menges and Waller, 1983;Willby et al, 2001 or herbivory;Elger et al, 2004), and on the other hand on population dynamics, and patterns of seed dispersal and vegetative regeneration (Marston et al, 1995;Hughes, 1997;Abernethy and Willby, 1999). Salo et al (1986) for example considered the fluvial dynamics of river systems to be fundamental in creating and maintaining high plant diversity.…”
Section: Introductionmentioning
confidence: 99%